Nós somos metade gente, outra de caranguejo: a dinâmica sócio-espacial da pesca do caranguejo (Ucides Cordatus) no maretório da RESEX marinha Caeté-Taperaçú Bragança/Pará - NASCIMENTO, Josinaldo Reis do (Instituto Federal de Educação, Ciência e Tecnologia do Pará, 2023)
The fisheries productivity of the Amazon coastis directly related to the dynamics of the mangrove forests. In these maretórios, the crab production chain (U. cordatus) has great socioeconomic importance. The aim ofthis article is to carry out an analysis of the socio-spatial dynamics of the crab production chain in the maretório of RESEX Caeté-Taperaçu, Bragança/PA. Between May and June 2017, and in October 2018, We interviewed 100 crab fishermen who work daily in the mangroves surrounding the PA-458 highway, and a sample of 20% of these were heard again in July 2021 in order to update economic data.. In recent decade, crab capture has evolved from a merely sporadic activity and self-consumption to a complex production chain. The intensification of the processing of crustacean meat, which has increasingly included womenin the production process, has increased fishing efforts, generating an average catch per unit of effort (CPUE) of 152 units/fisherman/day. The intermediary agents involved in the chain have contributed to the loss of independence and autonomy of the fishermen that tied to them, do not choose to whom and with whom to market the results of fisheries, increasingthe complexity of working relationships.